Pengaruh Edukasi Kesehatan Terhadap Tingkat Pengetahuan Mengenai Kebersihan Gigi dan Mulut Pada Siswa SDN 249 Astanaanyar Kota Bandung - Fauziah, Liliek (STIKES Ngesti Waluyo, 2024)
Dental and oral health issues frequently affect children between the ages of 6 and 14. Dental caries is the primary issue affecting the oral cavity. Several factors might impact an individual's dental and oral hygiene, such as socio-economic circumstances, age, gender, knowledge, surroundings, attitudes, and behaviors about dental and oral health. Therefore, it is necessary to implement health education initiatives specifically targeting dental and oral hygiene in youngsters. The study’s objective is to assess the impact of health education on the students' knowledge level of oral hygiene at Astanaanyar 249 Elementary School, Bandung City. The research methodology employs a quantitative experimental approach utilizing the One Group Pretest-Posttest Design. The population consists of 197 students in first and second grade. A total of 67 respondents were selected using the Proportional Random Sampling approach. The data gathering site was located at Astanaanyar 249 Elementary School in Bandung City. The research instrument employed a questionnaire supplemented with a PowerPoint presentation encompassing dental and oral hygiene data. The resulting validity test results were 0.96, indicating a high level of validity. Univariate data analysis examines frequency distribution, while bivariate analysis employs the Wilcoxon Signed Rank Test. The research findings indicated that the initial assessment revealed that a significant majority of respondents (68.7%) possessed a low level of knowledge. However, the follow-up assessment demonstrated that nearly all respondents (89.6%) had achieved a high level of knowledge. The Wilcoxon Signed Rank Test findings yielded a p-value of 0.000 < 0.05, indicating a statistically significant difference in knowledge before and after implementing dental and oral hygiene instruction. Recommendations for SDN 249 Astanaanyar, Bandung City, include implementing regular dental and oral hygiene health education programs to prevent and minimize the occurrence of dental caries proactively. Additionally, it is advised to establish partnerships with health organizations to facilitate the education program, as well as assessment of the oral and dental health of the students